Too far down [large type] - Connealy, Mary (Connealy, Mary. Cimarron legacy, 2017)
When an explosion at the mine kills workers and damages the CR Company, the Boden family is plunged deep into the heart of trouble yet again. As they try to identify the forces against them once and for all, Cole Boden finds himself caught between missing his time back in the east, and all that New Mexico offers-- namely, his family and cowgirl Melanie Blake.